The level of mental health among teachers of students with Down syndrome and its relationship to professional performance (Comprehensive Journal of Science, 2026)
This study aimed to identify the level of mental health among teachers of children with Down syndrome and to examine the relationship between mental health and professional performance, in addition to identifying differences according to certain demographic variables. The study adopted the descriptive analytical approach. The sample consisted of (43) female teachers working with children with Down syndrome in special education schools and centers in Tripoli, Al-Zawiya, and Sabratha, Libya, during the academic year 2025–2026, the researcher developed two instruments: a mental health scale covering physical, psychological, cognitive, and social dimensions, and a professional performance scale. The validity and reliability of the instruments were verified using expert validity, internal consistency, and Cronbach’s alpha coefficients, which indicated acceptable levels of validity and reliability, the findings revealed no statistically significant relationship between mental health and professional performance among teachers of children with Down syndrome. The results also showed statistically significant differences in some dimensions of mental health according to educational qualification, training courses, and marital status, while no significant differences appeared in other dimensions. Furthermore, training courses contributed positively to improving the psychological and cognitive dimensions of teachers’ mental health, whereas higher educational qualifications enhanced the cognitive dimension, the study recommended the importance of supporting the mental health of special education teachers through continuous counseling and training programs, improving the work environment, and providing psychological, social, and financial support to enhance professional performance and improve the quality of services provided to children with Down syndrome.
Keywords: Mental Health, Professional Performance, Special Education Teachers, Down syndrome, Special Education